Clinical and PROMIS Outcomes of Maisonneuve Fractures. Issue 1 (January 2022) - Andrews, Nicholas A.; Agarwal, Abhinav; Coffin, Megan; Fellows, Kenneth J.; James, Pate; Rallapalle, Vyshnavi; Harrelson, Whitt; Shah, Ashish
Category: Ankle; Trauma Introduction/Purpose: Torsional injury to the foot and ankle may result in high fibular fracture with disruption of the syndesmotic ligaments, interosseous membrane, and other associated injuries to medial, posterior structures of the ankle. High Fibular Fracture at the fibular neck is referred as Maisonneuve Fracture of Fibula (MFF). These injuries are often missed or misdiagnosed as ankle sprains. Most of the current classification consider MFF a variant of ankle fracture with disruption of syndesmosis and high fibular fracture {Lauge Hansen PER, AO C3, Weber type C}. Only a few articles have described associated injuries and surgical treatment outcomes. The study's primary aim is to evaluate the associated injuries of MFF and the outcomes of our treatment approach. Methods: All patients undergoing syndesmotic fixation (CPT 27829) at a large tertiary academic center from 2012-2020 were identified. In these 748 patients, patient radiographs were reviewed to identify patients with Maisonneuve fractures (AO-44C3). Medical records were reviewed for patient characteristics, energy information of original injury, operative variables, and complications. Radiographic reduction was assessed on standard radiograph with assessment of the tibiofibular clear space and tibiofibular overlap on AP and mortise views, talocrural angle, the medial clear space, shenton line, and fibular station. An abnormality in one of these parameters was considered an abnormal reduction. Patients were contact to complete PROMIS Physical function and Pain Interference postoperatively. A total of 24 patients with Maisonneuve fractures were identified and included in analysis. Eleven patients completed PROMIS outcomes measures for a response rate of 55%, as four patients were deceased or incarcerated at the time of survey. Results: The average age was 45.3 (16 SD) with a mean BMI of 31.3 (10.4 SD). Nineteen patients were male (79.2%) with only 5 females (20.8). The mechanism of injury was low energy in 16/24 patients (66.7%) leaving 8 (33.3%) patients with high energy mechanisms. In addition to the high fibular fracture, a total of 13 patients (54.2%) had a posterior malleolar fracture, 11 (45.8%) had a medial malleolar fracture, and 8 (33.3%) had a deltoid ligament injury. Seven patients (29.2%) received screw fixation compared to 14 patients (58.3%) with tightrope fixation. Three patients (12.5%) received both tightropes and screws. No patient developed wound complications, and two patients underwent reoperation. Abnormal reduction occurred in 5/24 patients (20.8%) at final clinical follow up. At a median of 20 months (25 IQR) postoperatively, the median PROMIS physical function and pain interference scores were 41.2 (13.0 IQR) and 52.8 (4.8 IQR), respectively. Conclusion: Maisonneuve fractures are an extremely rare ankle fracture variant with a diverse subset of injury patterns. Our results show the clinical outcomes of Maisonneuve fractures are largely satisfactory in terms of wound complications and intermediate term outcomes. While 21% of patients were determined to have abnormal reduction postoperatively, we are limited by the inherent difficulties of assessing syndesmosis on plain radiographs rather than advanced imaging. PROMIS outcome scores demonstrate Maisonneuve fractures patients are more impacted by loss of function than pain, but both are within a standard deviation of the population mean.